A Small-RNA-Mediated Feedback Loop Maintains Proper Levels of 22G-RNAs in C. elegans - Alicia K. Rogers; Carolyn M. Phillips (Cell Reports, 2020)
Summary: RNA interference (RNAi) is an essential regulatory mechanism in all animals. In Caenorhabditis elegans, several classes of small RNAs act to silence or license expression of mRNA targets. ERI-6/7 is required for the production of some endogenous small interfering RNAs (siRNAs) and acts as a negative regulator of the exogenous RNAi pathway. We find that the genomic locus encoding eri-6/7 contains two distinct regions that are targeted by endogenous siRNAs. Loss of these siRNAs disrupts eri-6/7 mRNA expression, resulting in increased production of siRNAs from other small RNA pathways because these pathways compete with eri-6/7-dependent transcripts for access to the downstream siRNA amplification machinery. Thus, the pathway acts like a small-RNA-mediated feedback loop to ensure homeostasis of gene expression by small RNA pathways. Similar feedback loops that maintain chromatin homeostasis have been identified in yeast and Drosophila melanogaster, suggesting an evolutionary conservation of feedback mechanisms in gene regulatory pathways.